Efficacy and Tolerability of a Fixed Combination of Thyme and Primrose Root in Patients with Acute Bronchitis - Gruenwald, Joerg; Graubaum, Hans-Joachim; Busch, Regina (Arzneimittelforschung, 2005)
In a double-blind, randomized, placebo-controlled, multicenter, prospective study, the clinical efficacy and tolerability of a fixed combination of thyme fluid extract and primose root tincture (Bronchicum® Tropfen) was investigated at a dosage of 30 drops (1 ml), taken orally five times daily. 150 outpatients (97 women, 53 men) suffering from acute, not previously treated bronchitis, lasting for less than 48 h, were randomized and treated with either verum (75 patients: 45 women, 30 men) or placebo (75 patients: 52 women, 23 men) over a time period of 7–9 days. 17 patients were excluded from the per-protocol (PP) collective because of either withdrawal from the trial (n = 2) or violations regarding examination time points and/or intake of the study medication (n = 15). The primary outcome criterion for efficacy assessment was the decrease of the Bronchitis Severity Score (BSS) at the end of the study compared to baseline. In the verum group, the BSS decreased from 12.0 ± 4.4 points at baseline to 1.0 ± 2.1 at study end compared to a decrease from 11.7 ± 4.3 points at baseline to 6.5 ± 4.8 at study end in the placebo group. The inter-group difference of 5.8 points was highly significant (p ≤ 10−3) in favour of the verum medication [Intention-to-treat (ITT) analysis]. At the end of the study, significantly more patients were symptom free in the verum group (58.7 %) than in the placebo group (5.3 %) as compared by the ITT analysis (secondary outcome criterion). For both parameters, the PP analysis showed comparable results. The results for the concomitant variables of efficacy support the high superiority of the verum medication compared to placebo. The therapeutic effect was more pronounced the stronger the severity of the acute bronchitis was (as proofed by a stratified evaluation based on severity grade). The tolerability was very good in both groups; neither serious adverse events nor clinically relevant findings in the safety parameters were observed. A total of 7 adverse events occurred, 2 in the verum group and 5 in the placebo group. One of the two adverse events in the verum group was considered to be possibly related to the intake of the study medication. Neither serious nor unknown adverse drug reactions were observed. Two drop-outs occurred during the study related to adverse events, both in the placebo group. In the global safety assessment, the tolerability of both medications was rated as “good” or “very good” by more than 90 % of the patients and physicians. In the present study, the fixed combination of thyme fluid extract and primrose root tincture was well tolerated and resulted in a clinically relevant and more pronounced decrease of the bronchitis symptoms (primary outcome criterion) and in shortening the duration of acute bronchitis (secondary outcome criterion) when compared to placebo.
Keywords: Bronchicum® Tropfen, clinical trial, efficacy, tolerability; Bronchitis, acute, severity score; Primose root; Thyme